Oocytes with aggregates of smooth endoplasmic reticulum may not affect reproductive outcomes in split IVF-ICSI insemination: a retrospective study - Yejuan Li; Jiajia Hu; Hui Lu; Zhiyong Lu; Jingjing Zhong; Lisen Shi (Frontiers in Endocrinology)
ObjectiveTo investigate the impact of smooth endoplasmic reticulum aggregates (SERa) in oocytes on embryological outcomes and clinical and neonatal outcomes during split IVF-ICSI cycles.MethodsA retrospective analysis was conducted using clinical data from January 2020 to December 2023 at the Reproductive Medicine Center of Hainan Women and Children’s Medical Center. Patients were divided into SERa+ and SERa- cycles based on the visibility of SERa after the removal of cumulus cells. Basic patient characteristics, embryological outcomes, clinical and neonatal outcomes were compared between the two groups.ResultsCompared to the SERa- cycles, the SERa+ cycles showed significantly higher levels of E2 on the day of hCG administration (P<0.01) and a significantly increased number of retrieved oocytes (P<0.01). In terms of embryological outcomes, the total D3 high-quality embryo rate was significantly higher in the SERa+ cycles (P<0.01). There was a significant increase in the D3 high-quality embryo rate for ICSI, but no difference in the D3 high-quality embryo rate for IVF. No significant differences were observed between the SERa+ and SERa- cycles in terms of βhCG positivity rate, clinical pregnancy rate, implantation rate, early miscarriage rate, live birth rate, preterm birth rate, newborn height, and weight (P>0.05). No congenital birth defects were found in either group.ConclusionThe occurrence of SERa in split IVF-ICSI cycles may be associated with increased E2 levels on hCG day, and the presence of SERa does not appear to affect in vitro fertilization, embryological, clinical, or neonatal outcomes.